Study of the effect exerted by fructo-oligosaccharides from yacon (Smallanthus sonchifolius) root flour in an intestinal infection model with Salmonella Typhimurium - Velez, Eva Maria del Mar (2013)
Beneficial effects of prebiotics like inulin and fructo-oligosaccharides (FOS) have been proven in health and nutrition. Yacon (Smallanthus sonchifolius), an Andean crop, contains FOS (50 – 70 % of its dry weight) and, therefore, is considered a prebiotic. Commercial FOS can up- regulate total secretory IgA (S-IgA) in infant mice, prevent infection with Salmonella in swine or enhance immune response for Salmonella vaccine in a mouse model. Previously, we found that administration of yacon root flour regulates gut microbiota balance and has immu- nomodulatory effects without inflammatory responses. The aim of the present paper is to analyse if yacon prevents enteric infection caused by a strain of Salmonella enteritidis serovar Typhimurium (S. Typhimurium) in a mouse model. BALB/c mice were supplemented with yacon flour (45d), challenged with S. Typhimurium and killed to study pathogen translocation, total and specific IgA production by ELISA, presence of IgA and other cytokines and Toll-like receptor 4 (TLR4) and clustor of differentiation 206 (CD206) receptors positive cells by immunofluorescence and histological changes. Yacon flour administration had a protective effect from 15 to 30 d of treatment. We found a peak of total S-IgA production without translocation of the pathogen for these periods. At 30 d, there was an increase in IL-6 and macrophage inflammatory proteins-1aþ cells and expression of the receptors CD206 and TLR4. Yacon flour did not have incidence in pathogen-specific S-IgA production. Longer periods (45 d) of administration had no protective effect. Therefore, yacon can prevent enteric infection caused by S. Typhimurium when given up to 30 d; this effect would be mediated by enhancing non-specific immunity, such as total S-IgA, that improves the immunological intestinal barrier.